Representation of Madness in Comedy Films and Television Series - Martynova Daria O. (Художественная культура, 2023)
This article is devoted to analysing humorous strategies and concepts of mental illness representation in contemporary comedy films and television series. It is worth noting that such a study is relevant in Russian discourse, since in the Western scientific literature of the last decade there have been separate interdisciplinary discussions about visualizations of mental pathologies in comedy films. For instance, the comedy film Me, Myself and Irene (2000) and the posters advertising it were subjected to a detailed analysis through the prism of the concept of cultural contextualization of comic madness. Having described the strategies of mental illnesses representation in contemporary comedy films and television series, the author concludes that there is a tendency for a comic interpretation of mental illnesses. Humorous elements appear even in melodramas, thrillers or horror films (for example, in The Shining or in A Beautiful Mind). This, however, can be explained: humorous interpretation of severe ailments makes it easier for viewers to perceive this ambiguous theme. Meanwhile, such an interpretation stigmatizes a disease, making others laugh at the character but not with them. In this regard, in the last decade, comedy films and television series on the topic of mental pathologies have been trying to develop strategies to combat stigmatization and trivialization of psychopathologies. As a result, the attempt to overcome the stigma in the context of visualization of mental pathologies has led to another, more global problem — the construction of cultural images that have turned into clichés.